Various psychiatric symptoms in a leukemia patient with human herpesvirus-6 encephalitis after umbilical cord blood transplantation - Ishikawa, Takayuki; Miyai, Hiroyuki; Otani, Kyohei; Matsuishi, Kunitaka; Shimomura, Yoshimitsu; Yonetani, Noboru; Tsurutani, Shigeru; Fukushima, Haruko (KOBE CITY HOSPITAL BULLETIN, 2021)
Human herpesvirus（ HHV）-6 is the most frequent cause of encephalitis in patients with hematopoietic stem cell transplant（HSCT） with significant morbidity and mortality. Major neurologic symptoms in patients with HHV-6 encephalitis include memorydisturbance, altered consciousness, and convulsions. However, psychiatric symptoms are infrequently associated with these patients.Here, we presented a post-HSCT patient with HHV-6 encephalitis, who manifested various psychiatric symptoms along withintractable pruritis, and intermittent pain in lower legs. The patient was diagnosed as having acute lymphocytic leukemia, whoreceived umbilical cord blood transplant after remission induction therapy and consolidation cure; the engraftment and maintenanceof complete remission were then confirmed. However, intermittent pain in both legs was exacerbated after the transplant along withconfused behavior, insomnia, and agitation. The diagnosis of HHV-6 encephalitis was made based on the detection of HHV-6 in thespinal fluid by polymerase chain reaction（ PCR）. Although the encephalitic symptoms, observed on examination, were resolvedby the administration of antiviral drugs, the patient continuously suffered psychomotor excitement with intermittent severe pruritusand pain, disorientation, and incoherent behavior. This case highlights that the symptoms characteristically appeared only one nighton a weekly basis, unlike the course of encephalitis or delirium.